Empowering Muslim Women-Owned Small and Medium-Scale Enterprises through Women Cooperative - Nurullaily, Shulhah; Yasid, Abu; Rahmawati, Lilik; Azka, Moh Shadam Taqiyyuddin (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2024)
This research aims to examine the influence of empowerment, business assistance, and entrepreneurial knowledge on business growth and household welfare in Small, and Medium Enterprises owned by Muslim women. The method used is partial least squares structural equation modeling with a sample of 254 Muslim women-owned SMEs who are members of the women's cooperative. The research findings indicate that empowerment and entrepreneurial knowledge play crucial roles as mechanisms for the business growth of Muslim women entrepreneurs and household welfare. Furthermore, the results also suggest that business assistance does not have a significant influence on the business growth of women Muslim entrepreneurs. Overall, the practical implications of these findings underscore the need for the development of more holistic empowerment programs that not only focus on business growth but also consider household welfare